2022
DOI: 10.1002/smll.202104934
|View full text |Cite
|
Sign up to set email alerts
|

In‐Situ Silica Xerogel Assisted Facile Synthesis of Fe‐N‐C Catalysts with Dense Fe‐Nx Active Sites for Efficient Oxygen Reduction

Abstract: In the past decade, atomically dispersed Fe active sites (coordinated with nitrogen) on carbon materials (FeNC) have emerged rapidly as promising single‐atom catalysts (SACs) for the oxygen reduction reaction (ORR) to substitute precious group metal (PGM) catalysts, owing to their earth abundance and low cost. Nonetheless, the production of highly active FeNC SACs is largely restricted by material cost, low product yield and difficulty of microstructure design. Herein, the authors demonstrate a facile in‐s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…have shown their promising potential in replacing the conventional noble metal cathode catalysts. [12][13][14][15][16][17][18][19][20][21][22] Several research groups have also achieved several exciting breakthroughs. For example, Sun et al 23 reported a Fe/N/C ORR catalyst prepared by pyrolysis under NH 3 that exhibited a half-wave potential of 0.78 V in 0.1 M HClO 4 .…”
Section: Introductionmentioning
confidence: 99%
“…have shown their promising potential in replacing the conventional noble metal cathode catalysts. [12][13][14][15][16][17][18][19][20][21][22] Several research groups have also achieved several exciting breakthroughs. For example, Sun et al 23 reported a Fe/N/C ORR catalyst prepared by pyrolysis under NH 3 that exhibited a half-wave potential of 0.78 V in 0.1 M HClO 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Although Pt-group metal (PGM)-based catalysts display considerable ORR activity and enable the practical implementation of fuel-cell technologies, their high cost, low availability, and consequent sustainability issues severely hinder their potential in commercial applications. Substantial efforts have been made toward the development of PGM-free materials, and among which, metal–nitrogen–carbon (M–N–C) catalysts that include dispersed earth-abundant metal atoms (e.g., Fe, Co, and Mn) have become increasingly popular. Such novel catalysts exhibit high per-site ORR activity and tolerance toward CO and CH 3 OH . In particular, Fe–N–C catalysts have been established as one of the most promising candidates, but there is still much room for improvement in ORR activity. , To improve their ORR performance, an in-depth understanding of the underlying reaction mechanisms of Fe–N–C catalysts is of vital importance.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, atomically dispersed transition metals coordinated with nitrogen distributed on carbon materials (M-NC), known as single-atom catalysts (SACs), have captivated increasing research interest for ORR catalysis as they possess advantages of low material cost and high catalytic activity, the latter of which benets from the high atom utilization and easily accessible active sites. [7][8][9] A vast array of synthetic strategies, including metal-organic frameworks (MOFs), wet impregnation and precipitation approaches, [10][11][12][13] have been developed for the preparation of SACs. Despite these signicant achievements, challenges, such as complicated synthetic routes and low product yields still severely restrict the large-scale production of high-performance SACs.…”
Section: Introductionmentioning
confidence: 99%